The Drafting a Cooperation Agreement According to Contact Law Standards in Indonesia at Ar-Royyan Hospital, Ogan Ilir Regency - Rusydi, Yudistira; Ardha, Dea Justicia; Usman, Abdul Hamid; Hayatuddin, Khalisa; Kasra, Helwan; Rani, Febrina (Unram Journal of Community Service, 2025)
Health is an essential part of societal well-being that must be pursued in line with Indonesia's aspirations as stated in the 1945 Constitution. This effort is carried out based on the principles of non-discrimination, participation, protection, and sustainability to develop human resources, enhance national competitiveness, and support national development. Written agreements in healthcare services are crucial to ensure optimal service delivery. This requires adequate healthcare facilities as the venue for implementing health efforts. In Indonesia, the agreement system follows an open principle that allows for the formation of agreements in accordance with existing laws or practices. The purpose of such agreements is to establish balanced cooperation and serve as a basis for resolving future issues. Through agreements, the involved parties are expected to uphold their promises, create clear legal relationships, and ensure protection and fairness for all.